2010
DOI: 10.1016/j.ceca.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The sarco/endoplasmic reticulum Ca2+ ATPase (SERCA) is the third element in capacitative calcium entry

Abstract: STIM1 and Orai1 are the main players in capacitative calcium entry (CCE). STIM1 senses [Ca(2+)] inside the endoplasmic reticulum (ER) and, when it decreases, opens Orai1, a store-operated calcium channel (SOC) in the plasma membrane that promotes Ca(2+) entry and increases cytosolic Ca(2+). The final destination of the entering Ca(2+) is the ER, which refills very efficiently (capacitatively) with it. We propose here that SERCA is the third element of CCE, to which is tightly coupled to favour rapid Ca(2+) pum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 43 publications
3
78
0
3
Order By: Relevance
“…Since SOCs opening depends on Ca 2+ content of the store, one may suggest that SERCA participates to its regulation. Consistent with this, SOCs open up when the leak of Ca 2+ from intracellular stores is not compensated with SERCA activity; SERCA inhibitors such as thapsigargin which prevent Ca 2+ uptake are commonly used to chemically induce SOC currents; several works have established that SERCA can cluster with STIM1 and Orai1 in various cellular types [41,42]. A n 1042 aa; 114.8 kDa …”
Section: Calcium Handling By the Sarco/endoplasmic Reticulum's Calciumentioning
confidence: 89%
“…Since SOCs opening depends on Ca 2+ content of the store, one may suggest that SERCA participates to its regulation. Consistent with this, SOCs open up when the leak of Ca 2+ from intracellular stores is not compensated with SERCA activity; SERCA inhibitors such as thapsigargin which prevent Ca 2+ uptake are commonly used to chemically induce SOC currents; several works have established that SERCA can cluster with STIM1 and Orai1 in various cellular types [41,42]. A n 1042 aa; 114.8 kDa …”
Section: Calcium Handling By the Sarco/endoplasmic Reticulum's Calciumentioning
confidence: 89%
“…It is established that translocation of STIM1 within the ER membrane to the ER-plasma membrane junctional sites, and formation of puncta following a decline in [Ca 2ϩ ] ER promotes STIM1 coupling with the CRAC channel pore-forming ORAI1 protein and CRAC channel opening (12,48,49,51,52). It was also shown that SERCA co-localize with STIM1 puncta following store depletion (53,54). Collectively, these observations suggest that following store depletion, SOCE via CRAC channels elevates [Ca 2ϩ ] i at the ER-plasma membrane junctional sites, whereas SERCA absorbs Ca 2ϩ that has entered the cell, resulting in an increase in [Ca 2ϩ ] ER .…”
Section: Ryr Expression and Function Are Up-regulated Upon Primary Humentioning
confidence: 99%
“…All these important functions are controlled by intra-ER free Ca 2þ , which integrates various signaling events and establishes a link between fast signaling, associated with ER Ca 2þ release=Ca 2þ uptake, and long-lasting adaptive responses relying primarily on the regulation of protein synthesis (14,22). Recently, SERCA has to been shown to be functionally coupled to the Ca 2þ sensor in the ER, called STIM, and Orai, a member of the TRP family, to allow efficient refilling of the ER (65).…”
Section: Calcium Binding Proteins and Transcriptional Networkmentioning
confidence: 99%